2010
DOI: 10.1007/s00330-010-1784-9
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive imaging of residual/recurrent nasopharyngeal carcinoma using whole-body MRI at 3 T compared with FDG-PET-CT

Abstract: Three-Tesla WB-MRI achieved a similar diagnostic capability to FDGPET-CT for the detection of residual/recurrent NPC. Both techniques have different advantages, and their combined interpretation can yield a slightly higher diagnostic capability. In clinical practice, 3-T WB-MRI can offer an accurate and comprehensive assessment of residual/recurrent NPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 41 publications
2
84
0
Order By: Relevance
“…In recent years, PET scans and PET-CT scans also have been described as prognostic tools in NPC. [33][34][35] Chan et al reported a positive correlation between metabolic parameters in PET-CT and T-classification at diagnosis. 33 Gordin et al demonstrated a better diagnostic performance with PET-CT scans compared with stand-alone PET scans or conventional diagnostic imaging studies.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, PET scans and PET-CT scans also have been described as prognostic tools in NPC. [33][34][35] Chan et al reported a positive correlation between metabolic parameters in PET-CT and T-classification at diagnosis. 33 Gordin et al demonstrated a better diagnostic performance with PET-CT scans compared with stand-alone PET scans or conventional diagnostic imaging studies.…”
Section: Discussionmentioning
confidence: 99%
“…The acceptable interval between PET/CT or PET and the reference standard (item 4) was not presented in 91% of the articles (5,14,15,(17)(18)(19)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). The common weaknesses were concentrated in the masking between the reference standard and index test (items 10 and 11).…”
Section: Assessment Of Study Quality and Publication Biasmentioning
confidence: 99%
“…10,11,13 There are still two studies in which 18 FDG PET-CT have the same sensitivity with gadolinium-enhanced MRI (0.89 vs 0.89 and 1.00 vs 1.00). 8,12 Our meta-analysis showed that gadolinium-enhanced MRI tended to have higher sensitivity (0.91 vs 0.84) than 18 FDG PET-CT. In the 10 included studies, 18 FDG PET-CT has similar specificity with gadolinium-enhanced MRI.…”
Section: Discussionmentioning
confidence: 83%
“…In two 15,20 of 10 articles, the study design was retrospective. In two studies (357 patients), 7,8 only patients with lung cancer were enrolled, in another two studies (102 patients), 10,19 only patients with colorectal cancer were enrolled, in four studies (511 patients), 9,12,13,18 only patients with head and neck cancer were enrolled, and in two studies (135 patients), 1,11 mixed patient populations were enrolled.…”
Section: Study Selection and Descriptionmentioning
confidence: 99%
See 1 more Smart Citation